Practical theologians" calling to serve in the field of gerontology - Theron, Petria M. (HTS teologiese studies, 2013)
The South African demographic statistics echo the global trend of an ageing population. This fact poses challenges to the country’s labour supply, to health care, retirement and intergenerational relations. The elderly are faced with specific challenges such as negative views regarding older people, discrimination and prejudice based on age, changing roles, the loss of a support system when children emigrate, financial problems, abuse and neglect, emotions of fear and depression, and the struggle to find meaning in life and suffering. The field of study that concerns ageing and older adulthood is called gerontology. Joan Erber defines it as ‘the study of the biological, behavioural, and social phenomena that occur from the point of maturity to old age.’ It is an interdisciplinary field where different disciplines seek to address the problems associated with ageing. Biologists focus on the biological processes of ageing, psychologists focus on aspects like mental abilities, personality and behaviour, whilst sociologists study the social roles, group behaviour and status of older people. The question may be asked what is being done regarding the spiritual and emotional needs of the elderly. This is the niche of practical theology, as indicated by one definition of practical theology that it is ‘a place where religious belief, tradition and practice meet contemporary experiences, questions and actions and conducts a dialogue that is mutually enriching, intellectually critical, and practically transforming’ according to Pattison and Woodward. The aims of this exploratory article are (1) to investigate to what extent research in practical theology has addressed the spiritual and emotional needs of the elderly and (2) to identify opportunities where practical theology may provide service in the field of gerontology.